Standardization Strategy for the Indonesian Language Proficiency Test (UKBI) in the PBSI Study Program at UMN Al-Washliyah - Nirmawan, Nirmawan; Hasibuan, Abdullah; Khairina, Isni (Westscience Press, 2025)
The urgency of UKBI in the form of a test for activists and education can be a benchmark for a person's language ability, similar to other language tests. The purpose of UKBI is expected to benefit relevant stakeholders such as the Indonesian government, test takers, associations and activists, lecturers, students, and the general public, as well as BIPA teachers on an ongoing basis, especially in terms of action plans and learning. The method used in this study is a qualitative descriptive method by providing a Google form, especially in the PBSI Study Program at UMN Al-Washliyah using the adaptive UKBI method, which includes the selection of four aspects of language skills. The targeted output of this study is how UKBI in the PBSI Study Program at UMN Al-Washliyah can be used as a requirement to participate in a green table hearing. The results of the study found that the UKBI exam in the Indonesian Language study program was considered important with a presentation of 100%, Lecturer knowledge about UKBI in the Indonesian Language study program reached 83.35, The combination of all types of UKBI reached 0.3%, the picture of the Indonesian language proficiency test can see the overall language ability of students 33.3%, and the picture of the Indonesian language proficiency test can improve student competence reaching 66.7. The novelty in this study regarding the UKBI concept applied to prospective PBSI graduates that has not been applied before so that graduates have competent abilities in four aspects of language skills